The action of selective CRAC channel blockers is affected by the Orai pore geometry - Derler, Isabella (Elsevier, 2013)
As the molecular composition of calcium-release activated calcium (CRAC) channels has been unknown for two decades, elucidation of selective inhibitors has been considerably hampered. By the identification of the two key components of CRAC channels, STIM1 and Orai1 have emerged as promising targets for CRAC blockers. The aim of this study was to thoroughly characterize the effects of two selective CRAC channel blockers on currents derived from STIM1/Orai heterologoulsy expressed in HEK293 cells. The novel compounds GSK-7975A and GSK-5503A were tested for effects on STIM1 mediated Orai1 or Orai3 currents by whole-cell patch-clamp recordings and for the effects on STIM1 oligomerisation or STIM1/Orai coupling by FRET microscopy. To investigate their site of action, inhibitory effects of these molecules were explored using Orai pore mutants. The GSK blockers inhibited Orai1 and Orai3 currents with an IC(50) of approximately 4 μM and exhibited a substantially slower rate of onset than the typical pore blocker La(3+), together with almost no current recovery upon wash-out over 4 min. For the less Ca(2+)-selective Orai1 E106D pore mutant, I(CRAC) inhibition was significantly reduced. FRET experiments indicated that neither STIM1–STIM1 oligomerization nor STIM1–Orai1 coupling was affected by these compounds. These CRAC channel blockers are acting downstream of STIM1 oligomerization and STIM1/Orai1 interaction, potentially via an allosteric effect on the selectivity filter of Orai. The elucidation of these CRAC current blockers represents a significant step toward the identification of CRAC channel-selective drug compounds.